Supplying of Active Fire Protection System (APAR) in Pulo Asem Area Jakarta Timur to Increase Safety Awareness for the Community - Sartika Rini; Hubertus Davy Yulianto (Bina Nusantara University, 2020)
Among the world record occupational safety and health (K3) accidents, the death toll in a fire is ranked just below natural disasters such as the earthquake and tsunami. Almost every type of building and almost every country in the world has experienced a history of devastating fires, whether in hotels, nightclubs, hostels, agriculture, shops or fuel depots, included a house. The question we must ask ourselves is ‘why has this tragedy occurred repeatedly and what have we learned from disasters over the past 100 years to strengthen preventive measures globally? There are three basic requirements that a fire can occur and get bigger: The presence of fuel or flammable materials; The existence of a lighter source; and The presence of oxygen in the air to support combustion. The ability to manage and reduce the risks associated with these three elements will greatly reduce the likelihood of a serious fire. So, our obligation as academics to provide knowledge and counseling about the danger of fire to the community so that they understand the danger of fire and can-do prevention and control, in addition to increasing awareness of fire hazards to create a safe and comfortable atmosphere in our environment.